Carrying Capacity of PLTA Koto Panjang Reservoir Based on Dissolved Oxygen For Fish Net Cage Culture in Batu Bersurat Village, XIII Koto Kampar Sub District, Kampar Regency, Riau Province - Tiara Priskila; Tengku Dahril; Asmika Harnalin Simarmata (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractCarrying capacity is an ability of aquatic environment to support the life of organism in aquaculture. This research aims to determined carrying capacity based on dissolved oxygen for fish net cage. It was conducted on June-July 2019 in PLTA Koto Panjang Reservoir Batu Bersurat Village. Sampling was determined at 3 locations namely Station 1 (tourism area and arround of this station there were palm’s plantation), Station 2 (restaurant and trees around the station) and Station 3 (floating net cages area). Each station there were three sampling points, namely in the surface (15 cm), 2 Secchi depth (330 cm) and 4 Secchi depth (660 cm).  Sampling was carried out 4 times, once/week. Water quality parameters measured were dissolved oxygen, free carbondioxide, BOD5, nitrate, phosphate, pH, temperature, transparency and depth. The results shown the concentration of dissolved oxygen in the waters ranged from 5.42-7.39 mg/L, nitrate 0.0568-0.0828 mg/L, phosphate 0.0592-0.0963 mg/L, free carbondioxide 5-12.99 mg/L, BOD5 4.03-8.90 mg/Ltransparency 153.5-161.25 cm and temperature 28.8-30.8 oC. Based on dissolved oxygen concentration indicates that the carrying capacity of inundation is 63,727 kg/yearand 141 units floating cage with size(6 x 6 x 6) m3.Keywords : Concentration, depth, floating net cages, water quality,BOD5